Exploring EFL Students’ Preferences in Extensive Reading - Irena Azka Azkia; Mansyur Srisudarso; Sumarta Sumarta (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
In the context of teaching language, a suitable teaching approach in the classroom affects teaching reading to language learners to be successful. The extensive reading can be used as an alternative approach to teach reading which provides many advantages for language learners specially to foster their reading skills. Many researchers have been conducted the extensive reading study, however, the majority of existing studies about the solution to teach language using extensive reading does not appear to be helpful to find students’ preference from the component of extensive reading. Therefore, this present qualitative study attempts to explore students’ preferences in the component of extensive reading. The findings present that the highest students' preference from the component of extensive reading is easy reading. Meanwhile, the smallest students’ preference from the component of extensive reading is about teacher orientation & guide. A future researcher is suggested to study extensive reading in other aspects besides exploring students' preference to increase the quality of next extensive reading implication to be better.